How Common Are Pulmonary and Hepatic Adverse Effects in Older Adults Prescribed Nitrofurantoin?. Issue 6 (17th March 2017) - Claussen, Karin; Stocks, Edward; Bhat, Deepa; Fish, Jason; Rubin, Craig D.
Abstract : Objectives: To determine the frequency of serious pulmonary and hepatic adverse events (AEs) in persons aged 65 and older prescribed nitrofurantoin. Design: Retrospective electronic health record (EHR) audit of nitrofurantoin prescriptions and associated AEs. Setting: Urban academic medical center. Participants: All inpatients and outpatients aged 65 and older prescribed nitrofurantoin from January 1, 2010, to December 31, 2014. Measurements: The number of nitrofurantoin prescriptions and pulmonary and hepatic AEs associated with nitrofurantoin use was acquired by data extraction from EHRs. Results: Of 3, 400 individuals aged 65 and older prescribed nitrofurantoin during the study period, 641 were identified as possibly having one of five targeted symptoms or disease complications (pulmonary and hepatic) associated with nitrofurantoin. After a detailed chart audit, 89% were deemed to have no adverse reaction, 7% had a minor side effect or allergy, and 3.9% met criteria for suspicion of a nitrofurantoin‐induced AE, five of whom were rated as being highly suspicious for nitrofurantoin toxicity; four of the five were identified with pulmonary toxicity and one with hepatotoxicity. Four of five of these individuals used nitrofurantoin chronically. Conclusion: Nitrofurantoin was prescribed for 3, 400 individuals aged 65 and older during the 5‐year study period. Serious side effects appeared to be uncommon, but chronic use appeared to be at greater risk.